Examining the links between livelihood sustainability and environmental protection in the anti-poverty relocation and settlement program areas: An empirical analysis of Shaanxi, China - Manman Guo; Manman Guo; Cong Li; Guangyu Wang; John L. Innes (Frontiers in Environmental Science, 2022)
Consistent with the 2030 agenda for sustainable development, China has initiated a large-scale anti-poverty relocation and settlement program (the ARSP), aiming to restore ecosystems and lift impoverished populations out of the poverty trap and into sustainable livelihoods. Unlike previous studies that focus on the population issues of the ARSP, we examine the links between livelihood sustainability and environmental protection (“livelihoods–environment”) in the ARSP areas. We found that the links are generally weak, with low levels of both livelihood sustainability and environmental protection. The disorder category is the most common in both the overall and the regional samples, with the mild and borderline disorder categories being the most common subcategories. The results varied regionally, and indicated that environmental problems can be more prominent in regions with fragile environments. Household-level distribution shows significant differences in the strengths of the links among different demographic groups, and regression results show that higher levels of average education, loan amount, and asset holdings, as well as lower proportions of the elderly and non-agricultural activities were associated with stronger links. These household factors influenced the links through different mechanisms.